Chronic consumption of a western diet modifies the DNA methylation profile in the frontal cortex of mice. Issue 2 (26th January 2018) - Yokoyama, Amy S.; Dunaway, Keith; Rutkowsky, Jennifer; Rutledge, John C.; Milenkovic, Dragan
Abstract : Western diet (WD; 42% kcal fat, 0.2% total cholesterol and 34% sucrose) alters DNA methylation in the frontal cortex of mice presenting one of the mechanisms by which consumption of a WD impairs cognitive function. Abstract : In our previous work in mice, we have shown that chronic consumption of a Western diet (WD; 42% kcal fat, 0.2% total cholesterol and 34% sucrose) is correlated with impaired cognitive function. Cognitive decline has also been associated with alterations in DNA methylation. Additionally, although there have been many studies analyzing the effect of maternal consumption of a WD on DNA methylation in the offspring, few studies have analyzed how an individual's consumption of a WD can impact his/her DNA methylation. Since the frontal cortex is involved in the regulation of cognitive function and is often affected in cases of cognitive decline, this study aimed to examine how chronic consumption of a WD affects DNA methylation in the frontal cortex of mice. Eight-week-old male mice were fed either a control diet (CD) or a WD for 12 weeks, after which time alterations in DNA methylation were analyzed. Assessment of global DNA methylation in the frontal cortex using dot blot analysis revealed that there was a decrease in global DNA methylation in the WD-fed mice compared with the CD-fed mice. Bioinformatic analysis identified several networks and pathways containing genes displaying differential methylation, particularly those involved in metabolism, cell adhesion and cytoskeleton integrity, inflammation and neurological function. In conclusion, the results from this study suggest that consumption of a WD alters DNA methylation in the frontal cortex of mice and could provide one of the mechanisms by which consumption of a WD impairs cognitive function.